EXAMINING DUAL ACADEMIC CREDIT AND THE LOCATION OF INSTRUCTION AS A PREDICTOR OF 12TH GRADE NAEP READING SCORES - Zhang, Mingyuan; Redmer, Rebekah (International Journal of Research -GRANTHAALAYAH, 2020)
This study explored 12th grade reading scores on the 2015 National Assessment of Educational Progress (NAEP) and how they relate to enrollment in dual credit college courses and the location in which they were taught. To gain a better understanding of dual credit attainment through various instructional delivery methods and the prediction of 12th grade reading scores, data was mined from the 2015 NAEP and presented in this descriptive research study. The findings of this study include for 12th grades students: (1) Students who earned ELA dual college credit delivered at their high school campus did not result in higher NAEP reading scores. (2) Students who earned ELA dual college credit delivered at a postsecondary campus did not result in higher NAEP reading scores. (3) Students who earned ELA dual college credit delivered through distance learning had higher NAEP reading scores when 11-25% of the 12th grade students enrolled. These findings make evident the high school campus or postsecondary campus dual credit courses for 12th grade students did not have an impact or can be used as a predictor on the NAEP reading test. The dual credit distance learning did have a positive impact on the 12th grade NAEP reading scores, specifically if a smaller percentage of students at the school enrolled, identifying that increasing access to dual credit may not always translate to increased college readiness and rigor.